THE EFFECT OF DIFFERENT BIO ACTIVATORS ON QUALITY COMPOST OF AGRICULTURAL WASTE - Pratiwi, Ellyza Yohana Putri; Suhartini; Sudrajat, Ahmad Kamal (Universitas Negeri Yogyakarta in collaboration with Perhimpunan Biologi Indonesia, 2023)
This study aims to determine the effect of using various bio activators on quality compost from agricultural waste and the best bio activators to obtain good quality compost from agricultural waste. This type of research is experimental with a Completely Randomized Design (CRD). The object of this research is compost from agricultural waste added with various bio activators: Tape Yeast, Tempe Yeast, Stardec, EM-4, and M-21 Decomposer. Each treatment consisted of 3 (three) replications. This study lasted for 75 days. The quality of compost is observed by physical parameters (temperature, humidity, pH, volume, weight, color, texture, smell), chemical parameters (carbon (C), nitrogen (N), C : N ratio, phosphorus (P), Kalium (K)), and composting time. Data were analyzed using One Way ANOVA and Kruskall Wallis Test. The results of this research on compost quality with physical parameters in all treatments had almost the same physical appearance, namely blackish brown color, texture or grain size of 2- 4mm, and had an earthy smell. Meanwhile, the analysis results on compost quality with chemicals showed a significant effect of different bio activators on the compost quality. Furthermore, the length of time for composting shows that the use of bio activators can affect the quality and speed up the composting time. EM-4 is the best bio activator to obtain the best compost quality.